Architecture and Solution of Lightweight TURN for C2C Communication - Aijun Wang; Bing Liu (Dianxin kexue)
An architecture and solution of lightweight TURN（TURN-Lite） which was suitable for C2C communication scenarios in complex network environment was described. It could simplify the communication processes used by current TURN solution and made full use of the data conversion and transfer capability of distributed data transfer devices（such as CGN/CDN）which had already deployed in current network, opened up network capabilities and provided efficient data transfer services for C2C communication applications developers.